2019
DOI: 10.1136/bmjopen-2018-028635
|View full text |Cite
|
Sign up to set email alerts
|

Factors supporting and constraining the implementation of robot-assisted surgery: a realist interview study

Abstract: ObjectiveTo capture stakeholders’ theories concerning how and in what contexts robot-assisted surgery becomes integrated into routine practice.DesignA literature review provided tentative theories that were revised through a realist interview study. Literature-based theories were presented to the interviewees, who were asked to describe to what extent and in what ways those theories reflected their experience. Analysis focused on identifying mechanisms through which robot-assisted surgery becomes integrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…These stakeholders have different and sometimes conflicting interests and perceptions on the benefits, risks, opportunities and limitations of integrating AI in healthcare. 3 9 There have been several scoping and systematic reviews capturing these various stakeholders’ perspectives on implementing AI in healthcare, 2 3 9 but they are mostly focusing on clinical outcomes and individual factors shaping AI adoption. However, none of these reviews focused on the wider organisational factors that can facilitate or hinder successful implementation of AI in the sector.…”
Section: Study Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…These stakeholders have different and sometimes conflicting interests and perceptions on the benefits, risks, opportunities and limitations of integrating AI in healthcare. 3 9 There have been several scoping and systematic reviews capturing these various stakeholders’ perspectives on implementing AI in healthcare, 2 3 9 but they are mostly focusing on clinical outcomes and individual factors shaping AI adoption. However, none of these reviews focused on the wider organisational factors that can facilitate or hinder successful implementation of AI in the sector.…”
Section: Study Rationalementioning
confidence: 99%
“…17 The authors jointly concluded that adequate funding would overall incentivise healthcare organisations as the introduction of AI requires significant financial expenditures and changes to operational processes. 3 10 17 18 Another reported organisational issue is related to a perceived loss of clinician control and autonomy, as some healthcare workers are concerned that policymakers, insurers, and administrators may use technology as a way to influence clinical decision making and actions. 18 Some studies also reported that the absence of a clear legal framework and relevant policy developments, especially when it comes to data protection and accountability for the care outcomes, can serve as potential organisational barriers for successful adoption of AI.…”
Section: Introductionmentioning
confidence: 99%
“…56 At the same time, it appears to be essential to include all participating parties in the process of implementation from the beginning. 57 To prevent tensions between ophthalmologists and GPs, it is essential to enhance communication between both parties and to share information. It should be communicated that a DR screening in primary care should not be a replacement but an addition to the existing system.…”
Section: Discussionmentioning
confidence: 99%
“…Since we can expect robots and humans to co-exist and collaborate, fostering trust for autonomous robots would be fundamental to their ability to perform their tasks. Policymakers will need to be cognizant of public's perspectives and implement effective strategies in launching human-robot co-working arrangements [64].…”
Section: Autonomymentioning
confidence: 99%